Penambahan Water Additive Kimchi Dapat Mencegah Infeksi Alami Flu Burung (Avian Influenza) pada Ayam Pedaging (THE SUPLEMENTATION OF WATER ADDITIVE KIMCHI COULD PREVENT NATURAL INFECTION OF AVIAN INFLUENZA IN BROILER) - Putra, I Putu Cahyadi; Wasito, Raden; Wuryastuty, Hastari (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
Subclinical infection of avian influenza (AI) in day old chick (DOC) has potential to interfere the success of vaccination programs. Therefore, an alternative ways to increase avian innate immunity in preventing the infection is necessary. The purpose of this study was to evaluate the effect of adding water additive (KimchiStock®) in preventing the occurrence of AI natural infection in DOC raising in commercial broiler farms. Fifty-five broiler DOCs, Cobb strains were used as experimental animals. Before the experiment begin, five DOCs were randomly selected, sacrificed and the lung were taken out for polymerase chain reaction (PCR) analysis on the matrix region. Fifty remaining DOCs were randomly divided into two: K1 (control) and K2 (treated) groups. K2 group were given 0.2% water additive (KimchiStock®) 5 days/ week for five weeks. Every week for five consecutive weeks, five chicken from each group were randomly selected for sera and lung collection. Sera samples were analyzed for antibody titer detection using haemagglutination inhibition technique. The results showed that there is no significant different in antibody titer between control and treated group. The majority of the antibody titer in this experiment were under 23. At week 4 the antibody titer of one chicken in treated group was 23 but no clinical sign was observed. Molecularly, there were no positive result detected from the lung of five DOCs at the beginning of the experiment and control group. While in the K2, positive result were detected on week 1 and 2 but without any clinical sign. Based on the research results could be concluded that adding 0.2% water additive KimchiStock® could prevent AI natural infection starting from week 3.